MENINGKATKAN KEMAMPUAN ANALOGI DAN GENERALISASI MATEMATIS SISWA SMP MENGGUNAKAN PEMBELAJARAN DENGAN METODE DISCOVERY - Maarif, Samsul (2012)
Indonesia is a country with high flora and fauna diversity. One of the most fauna diversity richness in Indonesia which have high attractiveness to collect even research object is insect especially butterflies. UPI's Botanic Garden is a natural laboratory district that used by the student of Biology major of FPMIPA UPI. UPI's Botanic Garden has many plants that can support butterflies diversity. Changing, rebuild dan renovation on Botanic Garden' mullet trigger some of plant disappear and making plant vegetation compotition in UPI's Botanic Garden change. The purpose of this research is collect the diurnal butterflies diversity data and the connection between butterflies and host plant existence. We hope the result of the research also can support and give the information that necessary for formulation plan of recommendation butterflies conservation, not only in UPI's Botanic Garden but also at the other place that have ability to become butterflies conservation area. Butterflies and larva diversity was recorded using standard walk method. The result shows there 40 butterflies species and 13 larva species, with the highest abundance is Delias belisama (0.158 ± 0.063). Meanwhile the lowest abundance is Melanitis leda (0.001 ± 0.003), Elymnias hypermnestra (0.003 ± 0.006), Euthalia monina (0.003 ± 0.006), Athyma nefte (0.003 ± 0.006) dan Amathusia phidippus (0.002 ± 0.003). Based on the research we found Cyrestis lutea that known an endemic species in Java and Bali. Whereas the number of butterflies host plant in UPI's Botanic Garden is 34 species. So the vegetation compotition of UPI's Botanic Garden can support the butterflies existence and diversity